Sistem Informasi Geografis Pemetaan Daerah Rawan Bencana Alam dengan Metode End User Development - Agus Susanto; Annas Setiawan Prabowo; Achmad Kategan; Akshal Dzikril Majid (P3M Politeknik Negeri Cilacap, 2022)
Cilacap is the largest district in Central Java with an area of 225,361 hectares. Topographically, Cilacap Regency is located at an altitude of 1-198 meters above sea level, stretching from west to east. With this condition, Cilacap Regency is an area that is prone to natural disasters such as floods, landslides and earthquakes. The area of Cilacap district along with the many areas prone to natural disasters makes the importance of a geographic information system mapping areas prone to natural disasters. With this system, it is hoped that the community and local governments can take precautionary measures before a natural disaster occurs in their area. The purpose of the research is to design a geographic information system for mapping natural disaster-prone areas for the Cilacap Regency web-based area with End User Development method. This method is used because it is able to produce a system that meets user needs directly. The testing the feasibility study of the system is conducted using the SUS (System Usability Scale) method. The results of this study are a geographic information system for mapping natural disasters and website-based evacuation points with the test results getting an average score of 72. This shows that the system can be implemented properly and is able to show the location of the natural disaster evacuation point areas more quickly as well as it is able to help the community and BPBD Cilacap in anticipating natural disasters.